2001
DOI: 10.1001/archinte.161.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate and Naproxen Are Synergistic for Development of Gastric Ulcers

Abstract: Both alendronate and naproxen can cause gastric ulcers. The combination appears synergistic. Alendronate should be used with caution in those who simultaneously require nonsteroidal anti-inflammatory drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 39 publications
2
29
0
1
Order By: Relevance
“…25 In addition to those studies, Graham et al have also shown in a randomized trial that 10 days of combined naproxen and alendronate medication had a synergistic effect on the development of gastric ulcer in healthy subjects: 8% for alendronate, 12% for naproxen, and 38% for patients on combined therapy. 28 Those data correlate with our data in the present study, where endoscopy was performed to evaluate drug-induced gastroduodenal injuries. Taking these endoscopic observations into consideration, the variation in data among the different studies that have been reported regarding the effect of bisphosphonates in the gastrointestinal tract might be result from differences in study designs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…25 In addition to those studies, Graham et al have also shown in a randomized trial that 10 days of combined naproxen and alendronate medication had a synergistic effect on the development of gastric ulcer in healthy subjects: 8% for alendronate, 12% for naproxen, and 38% for patients on combined therapy. 28 Those data correlate with our data in the present study, where endoscopy was performed to evaluate drug-induced gastroduodenal injuries. Taking these endoscopic observations into consideration, the variation in data among the different studies that have been reported regarding the effect of bisphosphonates in the gastrointestinal tract might be result from differences in study designs.…”
Section: Discussionsupporting
confidence: 90%
“…[18][19][20][21] A number of short-term endoscopy studies have been performed to investigate the association between bisphosphonate treatment and the development of mucosal erosive lesions of the upper gastrointestinal (GI) tract. [22][23][24][25][26][27][28][29] Although the two representative bisphosphonates, alendronate and resedronate, have been demonstrated to have upper gastrointestinal safety and tolerability profi les comparable to those of placebo in large clinical studies, [30][31][32][33][34][35] there have not previously been endoscopic studies in the clinical setting that comprise long-term concomitant use of ulcerogenic agents such as NSAID, corticosteroids, and bisphosphonates.…”
Section: Introductionmentioning
confidence: 99%
“…This patient was diagnosed as H. pylori positive and was concurrently using the bisphosphonate alendronate for the prevention of steroid-induced osteoporosis. Bisphosphonates are known to cause GI damage when administered alone [33], and it has been reported that co-administration of bisphosphonates increases the incidence rate of NSAID-induced ulcers [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates have been associated with increased risk of esophageal as well as gastroduodenal erosions and ulcers [1,2]. Because of this, patients are instructed to remain upright for 30-60 min after ingestion.…”
Section: Introductionmentioning
confidence: 99%